2010
DOI: 10.1590/s0036-46652010000300005
|View full text |Cite
|
Sign up to set email alerts
|

Differences in exoenzyme production and adherence ability of Candida spp. isolates from catheter, blood and oral cavity

Abstract: SUMMARYPhospholipase and proteinase production and the ability of adhesion to buccal epithelial cells (BEC) of 112 Candida isolates originated from oral cavity of HIV infected patients and from blood and catheter of intensive care unit patients were investigated. The proteinase production was detected by inoculation into bovine serum albumin (BSA) agar and the phospholipase activity was performed using egg yolk emulsion. A yeast suspension of each test strain was incubated with buccal epithelial cells and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 26 publications
4
22
0
1
Order By: Relevance
“…HIV-negative (21) 21 (100) previous studies (Ollert et al, 1995;Koga-Ito et al, 2006;Menezes et al, 2006;Costa et al, 2010;Sacristán et al, 2011). Similar to the results of Ollert et al (1995) and Wu et al (1996), we found increased expression of proteinase activity in isolates from HIV-infected individuals compared with HIV-uninfected subjects.…”
Section: Discussionmentioning
confidence: 97%
“…HIV-negative (21) 21 (100) previous studies (Ollert et al, 1995;Koga-Ito et al, 2006;Menezes et al, 2006;Costa et al, 2010;Sacristán et al, 2011). Similar to the results of Ollert et al (1995) and Wu et al (1996), we found increased expression of proteinase activity in isolates from HIV-infected individuals compared with HIV-uninfected subjects.…”
Section: Discussionmentioning
confidence: 97%
“…Secretion of enzymes by microorganism can play an important role in their pathogenesis [6,22]. Candidiasis is an opportunist fungal infection that is caused by several different species of Candida.…”
Section: Discussionmentioning
confidence: 99%
“…However, MANE et al 21 verified production of phospholipase and proteinase in only 59% and 89.7%, Among the isolates of non-albicans species identified in this study, 39% showed phospholipase activity and 21% exhibited proteinase activity. Previous studies also reported that proteinases and phospholipases are produced at high rates in C. albicans, whilst non-albicans Candida species usually present low rates of these enzymes 5,8 . No isolates of C. glabrata, C. lusitaniae or C. guilliermondii exhibited enzymatic activity.…”
mentioning
confidence: 83%